THE INFLUENCE FACTORS OF CONSUMER BEHAVIORAL INTENTION TOWARDS ONLINE FOOD DELIVERY SERVICES - Dian Novita; Nurul Husna (TECHNOBIZ : International Journal of Business, 2020)
The aims of this study is to investigate what are the influence factors of consumer behavioral intention toward online food delivery services (OFD). 200 valid questionnaires were collected to empirically test the research  model using partial least square (PLS) path modelling approach. The result imply that proposed hypotheses were supported except for the relationship between prior saving orientation and convenience motivation.